2016
DOI: 10.1002/ptr.5602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biological Activity ofOpuntia ficus indicaas a Tissue- and Estrogen Receptor Subtype-Selective Modulator

Abstract: Phytoestrogens are selective estrogen receptor modulators (SERMs) with potential for use in hormone replacement therapy (HRT) to relieve peri/postmenopausal symptoms. This study was aimed at elucidating the molecular mechanisms underlying the SERM properties of the extract of Korean-grown Opuntia ficus-indica (KOFI). The KOFI extract induced estrogen response element (ERE)-driven transcription in breast and endometrial cancer cell lines and the expression of endogenous estrogen-responsive genes in breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Oh et al [ 34 ] reported that GBE (50-200 mg/kg) administered to OVX rats for 6 weeks did not show agonistic effects on uterus. In addition, Opuntia ficus-indica (L.) Mill (250 and 500 mg/kg) extract, which contained quercetin, kaempferol, and isorhamnetin, had no agonistic effects on uterus in OVX rat models [ 9 ]. On the other hand, onion extract (30 mg/kg), which contained the same flavonoids as EGb761 (quercetin, kaempferol, and isorhamnetin), was found to have agonistic effects on the uteri of female Wistar immature mice [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oh et al [ 34 ] reported that GBE (50-200 mg/kg) administered to OVX rats for 6 weeks did not show agonistic effects on uterus. In addition, Opuntia ficus-indica (L.) Mill (250 and 500 mg/kg) extract, which contained quercetin, kaempferol, and isorhamnetin, had no agonistic effects on uterus in OVX rat models [ 9 ]. On the other hand, onion extract (30 mg/kg), which contained the same flavonoids as EGb761 (quercetin, kaempferol, and isorhamnetin), was found to have agonistic effects on the uteri of female Wistar immature mice [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…SERMs have organ-specific estrogenic activity and exhibit antagonistic activity in uterus and breast, and agonistic activity in bone, the cardiovascular system, and brain [ 8 ]. Furthermore, plant-derived products containing these compounds might have potential use for hormone replacement therapy (HRT) due to their ER-mediated molecular mechanisms [ 9 ]. GBE has been similarly reported to have estrogenic and antiestrogenic activities as determined by in vitro assay [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the effects of OFIE on gene expression and the activity of major hepatic DMEs, i.e., CYPs, and UGTs, were examined in OVX rats and human ex vivo and in vitro models. Previously, OFIE has been demonstrated as a promising candidate for botanical menopausal hormone supplement owing to its phytoestrogenic activity [ 12 ]; therefore, an OVX rat model with conditions similar to the estrogen-deprived state of postmenopausal women was utilized to investigate the modulating effects of OFIE on DMEs and to determine the DHI potential in the present study. Furthermore, cultured cell line and cell-free liver extracts such as microsomal fraction were used as tools to investigate the inhibitory and inductive effects of OFIE or the constituents comprising OFIE.…”
Section: Discussionmentioning
confidence: 99%
“…OFI fruits have been used for treating arteriosclerosis, diabetes, indigestion, inflammation, and other immune-related symptoms [ 10 , 11 ], implying that OFI-containing dietary products may be consumed by people who are likely to take medication to treat these conditions. In addition, we have previously demonstrated that the extract of freeze-dried OFI fruits (OFIE) can activate the estrogen receptor (ER)-mediated gene transcription in human cell lines and improve favorable lipid and glucose profiles in ovariectomized (OVX) rats [ 12 ]. The estrogenic activities of OFIE are attributed to the presence of flavonoid phytoestrogens such as isorhamnetin, kaempferol, quercetin, and their O -glycosides ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The next day, the cells were transfected with 0.25 μg of either pcDNA3-CAR or pcDNA3-PXR and 0.25 μg of a promoter luciferase plasmid (either pGL3-CYP2B6 or pGL3-CYP3A4) using Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) according to the manufacturer’s instructions. The transfected cells were grown for 24 h and treated with DMSO (vehicle); CITCO (6-(4-chlorophenyl)imidazo[2,1- b ] [1,3]thiazole-5-carbaldehyde O -3,4-dichlorobenzyl)oxime), a known CYP2B6 inducer (500 nM); rifampin, a known CYP3A4 inducer (10 μM); or flavanones, followed by incubation for an additional 24 h. The cells were harvested and luciferase activity was measured as described previously [ 43 ].…”
Section: Methodsmentioning
confidence: 99%